(Peer Review, Prosiding) Role of Soluble Heat Shock Proteins 70 in Severity of Dengue Infection - Dr. dr. Nurfadly, MKT. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Objective: to prove the role of soluble HSP 70 in the severity of dengue infection by comparing the level of solubI<fiSP 70 in patients who diagnosed as dengue fever (OF), deng!:]e hemon-ha ic fever (DJ- and I healthy people. Methods: Thi was a pro pective and longitudinal study, samples were taken by using consecutive sampling with a sample size were 22 OF patients, 20 DHF patients and 20 healthy people as a control group. Soluble HSP 70 in sertUn was measured by an enzyme-linked inununosorbent assay (ELISA). Results: The soluble I-ISP 70 was significantly increased (p=0.003) in DHF patients (0.33 ± 0.17 ng/ml) compared to in OF patients (0.149 ± 0.19 ng/ml) and control group (0.147 ± 0.37 ng/mJ), but there was not significantly increased (p=0.241) in OF patients compare within control group. Cone ion: This result suggesting that oluble HSP 70 may play important roles in the severity of dengue infection.